Diabetes, obesity and COVID‐19: A complex interplay. Issue 10 (28th July 2020) - Vas, Prashanth; Hopkins, David; Feher, Michael; Rubino, Francesco; B. Whyte, Martin
Abstract: With the accumulation of observational data showing an association of metabolic co‐morbidities with adverse outcomes from COVID‐19, there is a need to disentangle the contributions of pre‐existing macro‐ and microvascular disease, obesity and glycaemia. This article outlines the complex mechanistic and clinical interplay between diabetes and COVID‐19, the clinical and research questions which arise from this relationship, and the types of studies needed to answer those questions. The authors are clinicians and academics working in diabetes and obesity medicine, but the article is pitched to an audience of generalists with clinical experience of or interest in the management of COVID‐19.